Plasticity and Susceptibility of Brain Morphometry Alterations to Insufficient Sleep - Dai, Xi-Jian; Jiang, Jian; Zhang, Zhiqiang; Nie, Xiao; Liu, Bi-Xia; Pei, Li; Gong, Honghan; Hu, Jianping; Lu, Guangming; Zhan, Yang (Frontiers in Psychiatry, 2018)
Background: Insufficient sleep is common in daily life and can lead to cognitive impairment. Sleep disturbance also exists in neuropsychiatric diseases. However, whether and how acute and chronic sleep loss affect brain morphology remain largely unknown. Methods: We used voxel-based morphology method to study the brain structural changes during sleep deprivation (SD) at six time point of rested wakefulness, 20h, 24h, 32h, 36h SD, and after one night sleep in 22 healthy subjects, and in 39 patients with chronic primary insomnia relative to 39 status-matched good sleepers. Attention network and spatial memory tests were performed at each SD time point. The longitudinal data were analyzed using one-way repeated measures ANOVA, and post-hoc analysis was used to determine the between-group differences. Results: Acute SD is associated with widespread gray matter volume (GMV) changes in thalamus, cerebellum, insula and parietal cortex. Insomnia is associated with increased GMV in temporal cortex, insula and cerebellum. Acute SD is associated with brain atrophy and as SD hours prolonged more areas show reduced GMV, and after one night sleep the brain atrophy was restored and replaced by increased GMV. SD has accumulative negative effects on attention and working memory. Conclusions: Acute SD and insomnia exhibit distinct morphological changes of GMV. SD has accumulative negative effects on brain morphology and advanced cognitive function. The altered GMV may provide neurobiological basis for attention and memory impairments following sleep loss.